Palm Oil–Derived Natural Vitamin E α-Tocotrienol in Brain Health and Disease - Sen, Chandan K. (2010)
A growing body of research supports that members of the vitamin E family are not redundant with respect to their biological function. Palm oil derived from Elaeis guineensis represents the richest source of the lesser characterized vitamin E, α-tocotrienol. One of 8 naturally occurring and chemically distinct vitamin E analogs, α-tocotrienol possesses unique biological activity that is independent of its potent antioxidant capacity. Current developments in α-tocotrienol research demonstrate neuroprotective properties for the lipid-soluble vitamin in brain tissue rich in polyunsaturated fatty acids (PUFAs). Arachidonic acid (AA), one of the most abundant PUFAs of the central nervous system, is highly susceptible to oxidative metabolism under pathologic conditions. Cleaved from the membrane phospholipid bilayer by cytosolic phospholipase A(2), AA is metabolized by both enzymatic and nonenzymatic pathways. A number of neurodegenerative conditions in the human brain are associated with disturbed PUFA metabolism of AA, including acute ischemic stroke. Palm oil–derived α-tocotrienol at nanomolar concentrations has been shown to attenuate both enzymatic and nonenzymatic mediators of AA metabolism and neurodegeneration. On a concentration basis, this represents the most potent of all biological functions exhibited by any natural vitamin E molecule. Despite such therapeutic potential, the scientific literature on tocotrienols accounts for roughly 1% of the total literature on vitamin E, thus warranting further investment and investigation.